2021
DOI: 10.1021/acssuschemeng.0c08195
|View full text |Cite
|
Sign up to set email alerts
|

Helical Copper Redox Mediator with Low Electron Recombination for Dye-Sensitized Solar Cells

Abstract: Redox mediators play a major role in determining the photocurrent and photovoltage in dye-sensitized solar cells (DSSCs). Copper complexes are a good option for redox mediators but suffer from electron recombination. The traditional method is to add 4-(tert-butyl)pyridine (TBP) to the electrolyte, which is coordinated with the empty orbit of Ti, thereby slowing down the oxidized mediator's ability to capture electrons. However, this strategy will result in competitive coordination between the redox mediator an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…8%, suggesting that the use of these dinuclear species is a promising way forward. 126 (1) Compatibility between ruthenium(II) dyes and Cu 2+ /Cu + redox couples in order to achieve high photoconversion efficiencies remains a challenge. ] + , and these DSCs represent state-of-the-art combinations of ruthenium(II) dyes and copper-based redox mediators.…”
Section: Co 3+ /Co 2+ Redox Mediators: Ruthenium(ii) Dyesmentioning
confidence: 99%
See 1 more Smart Citation
“…8%, suggesting that the use of these dinuclear species is a promising way forward. 126 (1) Compatibility between ruthenium(II) dyes and Cu 2+ /Cu + redox couples in order to achieve high photoconversion efficiencies remains a challenge. ] + , and these DSCs represent state-of-the-art combinations of ruthenium(II) dyes and copper-based redox mediators.…”
Section: Co 3+ /Co 2+ Redox Mediators: Ruthenium(ii) Dyesmentioning
confidence: 99%
“…8%, suggesting that the use of these dinuclear species is a promising way forward. 126 [Cu I L] + ⇌ [Cu II L] 2+ + e − [Cu I 2 L 2 ] 2+ ⇌ [Cu I Cu II L 2 ] 3+ + e − [Cu I Cu II L 2 ] 3+ ⇌ [Cu II 2 L 2 ] 4+ + e − [Cu I 2 L 2 ] 2+ ⇌ [Cu II 2 L 2 ] 4+ + 2e − …”
Section: An Unfriendly Chemical Environment Within the Dsc: Enter The...mentioning
confidence: 99%
“…Lewis bases, such as TBP and N -methylbenzimidazole (NMBI), are frequently used as additives in DSC devices to enhance the overall cell performance. The enhancement observed with added Lewis bases is attributed to shifting the titania conduction band edge to more negative potentials and reducing the interfacial charge recombination rates by surface adsorption. , With most of the reported Cu-based RSs, TBP is known to coordinate with the Cu II species and even displace polydentate ligands, which has a significant impact on the redox potential as multiple redox species are produced, affecting the maximum achievable photovoltage and electron transfer kinetics. ,,, In this context, the effect of TBP on the [Cu­(bpyPY4)] 2+/+ redox couple was evaluated in the presence of different concentrations of the Lewis base. TBP was added in excess of 10 equivalents relative to [Cu­(bpyPY4)] 2+ in solution to match the conditions used in the devices described below.…”
Section: Resultsmentioning
confidence: 58%
“…In various examples it has been shown that appropriate functionalization of linear oligothiophenes with polar moieties such as peptides [31][32][33] or poly(ethylene oxide) 34 promote the formation of supramolecular nanostructures. Metal-assisted organization of symmetric OT-phen-based ligands into a dimeric dihelical arrangement should benefit from intermolecular π-π stacking interactions of the linear OT-linkers on one hand and from the preference of spherical d 10 -Cu(I) ions to adopt a pseudotetrahedral (D2d) coordination with α,α'-diamine ligands such as phen on the other hand.…”
Section: Accepted Manuscriptmentioning
confidence: 99%